2012
DOI: 10.1139/h11-156
|View full text |Cite
|
Sign up to set email alerts
|

Repeated high-intensity Wingate cycle bouts influence markers of lymphocyte migration but not apoptosis

Abstract: Studies have shown significant changes in lymphocytes during continuous exercise, but little has been shown on the effect of repeated high intensity bouts. This study was designed to examine the effect of repeated intermittent bouts on lymphocyte subset cell count, apoptosis, and migration. A series of 6 Wingate anaerobic cycle tests were performed by participants (N = 8) with blood samples attained before, immediately following, and after a designated recovery period (excess postexercise oxygen consumption (E… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

2
29
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(32 citation statements)
references
References 33 publications
2
29
1
Order By: Relevance
“…Lymphocytopenia, defined as a significant decrease in circulating lymphocytes, was not seen in this study as it has been seen in previous studies [2,4,10]. This could possibly be due to the fact that previous studies which saw this effect found the significance exclusively in CD8 T cells at the highest exercise intensities utilized within their respective exercise protocols [2,4,10], whereas we analyzed whole lymphocytes, which include CD4, CD8, memory T cells, naïve B cells, B plasma cells, and memory B cells. A synthesis of these 2 findings may suggest a significant increase in one or more types of circulating lymphocytes in the post-exercise period, which would result in the effects seen here.…”
supporting
confidence: 59%
See 3 more Smart Citations
“…Lymphocytopenia, defined as a significant decrease in circulating lymphocytes, was not seen in this study as it has been seen in previous studies [2,4,10]. This could possibly be due to the fact that previous studies which saw this effect found the significance exclusively in CD8 T cells at the highest exercise intensities utilized within their respective exercise protocols [2,4,10], whereas we analyzed whole lymphocytes, which include CD4, CD8, memory T cells, naïve B cells, B plasma cells, and memory B cells. A synthesis of these 2 findings may suggest a significant increase in one or more types of circulating lymphocytes in the post-exercise period, which would result in the effects seen here.…”
supporting
confidence: 59%
“…Although not measured in the present investigation, previous studies have shown lymphocyte cell count to be influenced by changes in catecholamine levels [6]. Lymphocytopenia, defined as a significant decrease in circulating lymphocytes, was not seen in this study as it has been seen in previous studies [2,4,10]. This could possibly be due to the fact that previous studies which saw this effect found the significance exclusively in CD8 T cells at the highest exercise intensities utilized within their respective exercise protocols [2,4,10], whereas we analyzed whole lymphocytes, which include CD4, CD8, memory T cells, naïve B cells, B plasma cells, and memory B cells.…”
contrasting
confidence: 47%
See 2 more Smart Citations
“…On the other hand, the lymphocytopenia observed post-exercise could be a result of immune cell migration [42], apoptosis [11] or both [24]. Considering the effect of 6 series of Wingate anaerobic cycle tests on lymphocyte apoptosis and migration, it was reported that post-exercise lymphocytopenia was a result of immune cell migration, particularly the suppressor T cell subset, rather than apoptosis [11]. Observations based on intensive treadmill running protocol at 80 % maximal O 2 uptake, provided evidence that the mobilized lymphocytes appeared to extravasate the peripheral blood compartment [42].…”
Section: Hematological Changes and Exercisementioning
confidence: 99%